To Compete or Cooperate? A Case Study of Innovation and Creativity Labs in Berlin - Daniel Feser (Journal of the Knowledge Economy, 2022)
Innovation intermediaries provide support during innovation processes and contribute to clients' innovativeness. In a growing body of literature, innovation intermediaries are considered as knowledge brokers and boundary spanners in regional innovation systems. While previous studies have highlighted insights into intermediaries' impact on clients, observations of their internal policies and working mechanisms remain scarce. Based on a case study of Berlin-based innovation and creativity labs, this paper sheds light on the innovation strategies chosen by intermediaries. I find that a distinct dualism of cooperation and competition shapes the innovation strategies of innovation intermediaries. The growing number of competitors and a lack of transparency shape the role of regional policy that offers information and market coordination. I present policy recommendations based on the results.
Keywords: 330; Regional innovation systems; Innovation intermediation; Innovation strategy